HULC: an oncogenic long non‐coding RNA in human cancer - Yu, Xin; Zheng, Heyi; Chan, Matthew T.V.; Wu, William Ka Kei (Journal of cellular and molecular medicine, 2017)
Highly up‐regulated in liver cancer (HULC) was originally identified as the most overexpressed long non‐coding RNA in hepatocellular carcinoma. Since its discovery, the aberrant up‐regulation of HULC has been demonstrated in other cancer types, including gastric cancer, pancreatic cancer, osteosarcoma and hepatic metastasis of colorectal cancer. Recent discoveries have also shed new light on the upstream molecular mechanisms underlying HULC deregulation. As an oncogene, HULC promotes tumorigenesis by regulating multiple pathways, such as down‐regulation of EEF1E1, promotion of abnormal lipid metabolism, and up‐regulation of sphingosine kinase 1. Pertinent to clinical practice, a genetic variant in the HULC gene has been found to alter the risk for hepatocellular carcinoma and oesophageal cancer, whereas cancer patients with high or low expression of HULC exhibit different clinical outcome. These findings highlighted the pathogenic role and clinical utility of HULC in human cancers. Further efforts are warranted to promote the development of HULC‐directed therapeutics.